Optimization of Cultural Conditions for the Production of Pectinase from Selected Fungal Strain - Dhital, Rajiv; Panta, Om Prakash; Karki, Tika Bahadur (Journal of Food Science and Technology Nepal, 2014)
Pectinase are the group of enzymes that catalyze the degradation of pectin substances through de-polymerisation and de-esterification. This study is concerned on the isolation, screening and selection of suitable strain of pectinolytic organism and optimization of cultural conditions for the biosynthesis of pectinase. From the soil samples collected from Lalitpur, Kathmandu, Gulmi, Manang and Dang, 18 fungal colonies were isolated on the basis of halozone formation on Potato dextrose agar and identified. Enzyme production was carried out by submerged state fermentation. The partially purified enzymes showing higher pectinolytic activity were characterized on the basis of temperature of incubation, substrate concentration and pH of the substrate by Dinitro salicylic acid assay (DNSA) method. The fungal isolate showing highest enzyme activity was subjected to optimization of culture medium for the production of enzymes. On optimization, it was found that MG1 (Aspergillus niger) was the most potent strain at 1.5% substrate (pectin) concentration, pH 4.5 and temperature of 30°C. On the enzyme application, the yield of the orange juice, Total Soluble Solid and absorbance increased as the concentration of the enzyme increased and hence increasing the possibility of being used commercially for maximum pectinase production. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11752 J. Food Sci. Technol. Nepal, Vol. 8 (65-70), 2013